2020
DOI: 10.1002/bies.202000053
|View full text |Cite
|
Sign up to set email alerts
|

The Hair Follicle as an Interdisciplinary Model for Biomedical Research: An Eclectic Literature Synthesis

Abstract: Skin is a comparatively accessible organ possessing many conserved regulatory and signaling pathways, drawing researchers from varied fields toward its study. Hair follicle (HF) biology in particular has expanded rapidly over the preceding decade, helping to shape and develop scientific knowledge across diverse areas of biomedical research, beyond the skin. The hope in compiling this review is to inspire more researchers to utilize the HF as an instructive biological model, bringing with them fresh perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Here, we will made a brief description, limited to those tissue structures exhibiting relevant outcomes after staining with RGB trichrome. Special emphasis will be devoted to the staining characteristics of the hair follicle, as it constitutes an interdisciplinary model for biomedical research 9 , 10 , 16 . All figures in this study are stained with RGB trichrome unless otherwise indicated in the figure legend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will made a brief description, limited to those tissue structures exhibiting relevant outcomes after staining with RGB trichrome. Special emphasis will be devoted to the staining characteristics of the hair follicle, as it constitutes an interdisciplinary model for biomedical research 9 , 10 , 16 . All figures in this study are stained with RGB trichrome unless otherwise indicated in the figure legend.…”
Section: Resultsmentioning
confidence: 99%
“…This makes the skin a paradigm for regenerative medicine, for the study of the interactions between epithelial and mesenchymal cells, and between cells and extracellular matrix 2 , 6 , 7 . Among the skin appendages, hair follicles have received much attention in biomedical sciences, due to their functional and structural complexity, their self-renewing activity, their content of several stem cell populations that can regenerate the different skin cell lineages 810 , and their social relevance due to their impact in one’ ss appearance.…”
Section: Introductionmentioning
confidence: 99%
“…The Notch signaling pathway is essential for maintaining follicle structure and facilitating follicle formation and reepithelialization 13 . Ultimately, determining the morphology and development of the HFs 14 , 15 . The morphogenesis and development of HFs proceed through three sequential stages: induction (production of hair placodes), organogenesis (downward growth of hair placodes), and cytodifferentiation (morphogenesis of HFs).…”
Section: Hf Morphogenesis and Developmentmentioning
confidence: 99%
“…Hair follicles (HFs) are a crucial component of human skin physiology and homeostasis [ 1 4 ]. These immune-privileged mini-organs are populated by a much richer microbiome than the human skin surface, whose microbiome is rapidly repopulated by the HF microbiome following skin disinfection [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%